2018
DOI: 10.1002/jcp.26295
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves nicotine reward‐associated cognitive behaviors and related α7 nAChR‐mediated signal transduction in adolescent rats

Abstract: The adolescent brain is vulnerable to long-lasting cognitive disturbances resulting from nicotine exposure. Although exercise has been used as an intervention for ameliorating cognitive deficits in various disorders, the effect on cognitive changes induced by nicotine exposure and its underlying mechanisms remain unclear. The purpose of this study was to investigate the effects of exercise on nicotine reward-associated cognitive behaviors in adolescent rats subjected to nicotine conditioned place preference pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…For example, mice with one or four weeks of access to running wheels immediately after cocaine conditioning showed reduced CPP as compared to sedentary controls (Mustroph et al 2016). In addition, treadmill running has been reported to reduce nicotine CPP in mice when introduced after conditioning (Zhou et al 2018).…”
Section: Conditioned Place Preferencementioning
confidence: 99%
“…For example, mice with one or four weeks of access to running wheels immediately after cocaine conditioning showed reduced CPP as compared to sedentary controls (Mustroph et al 2016). In addition, treadmill running has been reported to reduce nicotine CPP in mice when introduced after conditioning (Zhou et al 2018).…”
Section: Conditioned Place Preferencementioning
confidence: 99%
“…Furthermore, in addition to the presynaptic nAChRs, nicotine also stimulates the postsynaptic nAChRs in the dopamine neurons of the VTA, enhancing the release of dopamine in the nuclear accumbens, which is thought to be responsible for reinforcing dependence of nicotine ( Tiwari et al, 2020 ). In a previous study, it has been shown that, compared with light- and high-intensity exercise interventions, a moderate-intensity exercise intervention has the most positive effect in terms of improving cognitive dysfunction and perturbed expression of nAChRs and downstream signaling molecules in the prefrontal cortex, which are important for depression and anxiety ( Zhou et al, 2018 ). This result might indicate a possible mechanism contributing to the finding in the present meta-analysis, in which moderate-intensity exercise was found to have the best attenuating effect on depression and anxiety in people with SUDs.…”
Section: Discussionmentioning
confidence: 99%
“…Treadmill running after subcutaneous injections of nicotine prevents cognitive impairment, such as reduced short‐term memory and spatial learning ability, induced by withdrawal (Park et al., 2019). Another study showed that high‐ and moderate‐intensity exercise on a treadmill improved learning and memory, and the inhibitory control, in adolescent rats that were administered nicotine subcutaneously (Zhou et al., 2018). Moreover, involuntary exercise combined with bupropion reduced depressive‐ and anxiety‐like behaviors in rats with nicotine history (Motaghinejad et al., 2016).…”
Section: Effects Of Exercise On Substance Use Disordersmentioning
confidence: 99%
“…This study also suggests that the exercise‐induced decrease in motivation during self‐administration is due to a reduction in the reinforcing effects of nicotine (Sanchez et al., 2015). In addition, involuntary exercise, such as motor‐driven treadmill and forced swimming, induced attenuation in nicotine's rewarding effects, decreased nicotine sensitivity, and reestablished cognitive functions impaired by nicotine intake (Alzoubi et al., 2019; Park et al., 2019; Peck et al., 1991; Zhou et al, 2018).…”
Section: Effects Of Exercise On Substance Use Disordersmentioning
confidence: 99%